AgNOR counts and determination of malignancy in stromal tumours of the stomach and small intestine. - Beer, T. W. (1992)
Twenty four primary stromal tumours of the stomach and small intestine were investigated by silver staining of interphase nucleolar organiser regions (AgNORs) in an attempt to obtain an objective criterion for prediction of malignant tumour behaviour. Malignant tumours tended to have higher AgNOR counts than their benign counterparts, but this increase was small and there was some overlap between the two groups. There was a correlation between the mean AgNOR count and the mitotic count. There was no correlation between tumour size and these two measurements. This study suggests that in these stromal tumours the AgNOR count is not a useful independent predictor of malignant behaviour.